Urothelial generation and regeneration in development, injury, and cancer. Issue 4 (2nd March 2017) - Wang, Caihong; Ross, Whitney Trotter; Mysorekar, Indira U.
Abstract : Homeostatic maintenance and repair of the urothelium upon injury are required for a functional bladder in both healthy and disease conditions. Understanding the cellular and molecular mechanisms underlying the urothelial regenerative response is key to designing strategies for tissue repair and ultimately treatments for urologic diseases including urinary tract infections, voiding dysfunction, painful bladder syndrome, and bladder cancer. In this article, we review studies on urothelial ontogeny during development and regeneration following various injury modalities. Signaling pathways involved in urothelial regeneration and in urothelial carcinogenesis are also discussed. Developmental Dynamics 246:336–343, 2017 . © 2016 Wiley Periodicals, Inc. Key Findings: In this article, we review studies on urothelial ontogeny during development and regeneration following various injury modalities. Signaling pathways involved in urothelial regeneration and in urothelial carcinogenesis are also discussed.